2021
DOI: 10.1038/s41467-021-27078-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of epigenetic regulation with gene therapy-mediated immune checkpoint blockade induces anti-tumour effects and immune response in vivo

Abstract: Immunotherapy has become a powerful cancer treatment, but only a small fraction of patients have achieved durable benefits due to the immune escape mechanism. In this study, epigenetic regulation is combined with gene therapy-mediated immune checkpoint blockade to relieve this immune escape mechanism. PPD (i.e., mPEG-b-PLG/PEI-RT3/DNA) is developed to mediate plasmid-encoding shPD-L1 delivery by introducing multiple interactions (i.e., electrostatic, hydrogen bonding, and hydrophobic interactions) and polyprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 65 publications
0
44
0
Order By: Relevance
“…Immunotherapy has made revolutionized impacts on anti-tumor therapy, which performs its capacity by acting on specific molecular markers, including PD1, PD-L1, and CTLA-4. Nevertheless, only a subset of patients displayed a curative response ( 17 ). As a common targeted therapy, multi-kinase inhibitors (tyrosine kinase inhibitors, TKIs) perform tumor suppression via restraining tumor angiogenesis and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy has made revolutionized impacts on anti-tumor therapy, which performs its capacity by acting on specific molecular markers, including PD1, PD-L1, and CTLA-4. Nevertheless, only a subset of patients displayed a curative response ( 17 ). As a common targeted therapy, multi-kinase inhibitors (tyrosine kinase inhibitors, TKIs) perform tumor suppression via restraining tumor angiogenesis and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that tumors with higher expression of LSM12, LSM14A, and LSM14B had higher expression of tumor-related immune checkpoints (e.g., PD-L1, B7-H3, and PVR), which are important for the immunosuppressive phenotype in malignancies ( Figures 8A–C ) ( 20 24 ). Furthermore, ImmuneCellAI ( ) was used to predict the therapeutic response to immune checkpoint blockade (ICB).…”
Section: Resultsmentioning
confidence: 51%
“…The spleen, the largest immune organ, plays a critical role in systemic immunity [ 36 38 ], and the lymphocytes isolated from it were used here to evaluate the immune response of Nano PCPT+PIMDQ . The results demonstrated that Nano PCPT+PIMDQ effectively boosted the beneficial immune function of the spleen.…”
Section: Resultsmentioning
confidence: 99%